Poste Restante, Dead Letters and General Delivery (Hawthorne Writes Home from Rome) - Melville, Stephen (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1992)
The question of culture in America and the conditions under which it becomes possible to say "we", with particular reference to Hawthorne's Marble Faun.